Survival Of The Prettiest: Why Beauty Matters - An Evolutionary Account - Tadinac, Meri (2008)
It is estimated that Americans now spend more each year on beauty than they do on education. There are endless examples across cultures of numerous sacrifices, even very painful ones, people are ready to suffer for the sake of being beautiful. Why is it so? Some social scientists argue that we are seduced by the powerful marketing campaigns of the multinational cosmetic companies and the media. But they conveniently forget that throughout history art has celebrated the ideal beauty. The cosmetic industry is not a modern invention – the Egyptians had most of the cosmetics we have today. Evolutionary psychology states that beauty is neither a cultural construct nor an invention of the fashion industry, and appreciating beauty is not learned but is rather a biological adaptation. Two observations support this notion: first, people in different cultures generally agree on which faces are attractive ; second, preferences emerge early in life, before cultural standards of beauty are likely to be assimilated Human beauty standards reflect our evolutionary distant past and emphasize the role of health assessment in mate choice. Just as our prehistoric ancestors had learnt to distinguish nutritious food from poisonous one, they devised by instinct methods of judging gene quality in their mates. Part of our beauty perception may be programmed into our brain circuits and has been throughout the history of humankind, since basic features that construct human beauty have tended to reflect the adaptive fitness of the bearers of these features. Many physical characteristics that men and women find attractive serve as cues to health, good genes and/or high fertility in the other sex. The physical characteristics that are most admired, such as clear and smooth skin, uniform in colour, gleaming lustrous hair, etc., are all indicators of good physical health, and a clear sign that the individual will make a good mating partner. Such preferences could also increase offspring viability, such as heritable resistance to disease. In the course of evolution, the people who noticed these signals and desired their possessors had better reproductive success. We are their descendants. Therefore, a conventional wisdom that beauty is in the eyes of the beholder should take into account that those eyes and the brains behind them have been shaped by human evolution, or, as Symons (1995) says: “ Beauty is in the adaptations of the beholder” .
Projekt MZOS
ENG